EFEKTIVITAS MEDIA QUIZALIZE TERHADAP MOTIVASI BELAJAR EKONOMI SISWA KELAS XI SMA BAWARI - Viona, Viona Viona; Witarsa, Witarsa; Syahrudin, Husni (Universitas Tanjungpura, 2025)
The purpose of this study is to evaluate the effectiveness of the Quizalize learning platform in enhancing students' learning motivation in Economics among eleventh-grade students at SMA Islam Bawari Pontianak. A total of 68 students participated, with 34 students from class XI-1 assigned to the experimental group and 34 from class XI-4 assigned to the control group. The inquire about utilized a quasiexperimental plan with a nonequivalent control gather structure. Data analysis involved tests of normality, homogeneity, hypothesis testing, and effect size calculation. The posttest effect size analysis yielded a score of 4.985, indicating a very large effect. Furthermore, the independent sample t-test revealed a significant value of 0.018, which is less than 0.05, suggesting a statistically significant difference in learning motivation between students using Quizalize and those taught through conventional methods. It can be concluded that the use of Quizalize significantly influences students' learning motivation in grade XI at SMA Islam Bawari Pontianak.